Stefan Żeromski. Tożsamości, poetyki, style odbioru - Sobieraj, Tomasz (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
This article is a review of the collective monograph Stefan Żeromski. Kim był? Kim jest? edited by Zdzisław Jerzy Adamczyk. The book contains thirty essays written by experts in their respective fields. Both Stefan Żeromski’s views and many aspects of his writings were here thoroughly examined. It is said that Żeromski, one of the most influential Polish writers at the end of the nineteenth and at the beginning of the twentieth century, strongly affected Polish culture. The contributors of the book undoubtedly proved the thesis.